DEVELOPMENT OF CREATIVE ABILITIES OF PRIMARY SCHOOL STUDENTS - AS A PEDAGOGICAL PROBLEM. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This article provides the necessary information and resources on the tasks of a teacher to be used in order to develop creative abilities in primary school students. Based on the information provided in the article, teachers and parents can get the necessary recommendations for themselves